Cleanly to godly, sudsy to saintly: the ranges of Hittite suppi- - Puhvel, Jaan (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
The adjective suppi- is an important yet problematic item of Hittite vocabulary. While amply attested and derivationally endowed, it seems notably devoid of matching cognates in the rest of Anatolian, raising the probability of unilingual proliferation in a specific sociocultural orbit, that of religious and ritual texts which comprise a disproportionate segment of the Hittite corpus.